2017
DOI: 10.5267/j.ijdns.2017.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Recent trend of e-business in Canada

Abstract: Canadian enterprises are increasingly implementing Internet based e-business technologies such as websites, web-based procurement, and e-commerce to reduce their cost and increase their productivity. While there have been several studies in different countries to locate the determinants of e-business adoption, the newness of business could preclude much understanding of the factors, which influence the evolution of e-business within firms. This paper performs a review on recent studies on the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The results of data analysis shows that H5 is rejected, there is a negative and not significant influence on cost on the sustainability of MSMEs. This is in line with the research of (Orouji & Kafashan, 2017), which states that the sustainability of MSMEs requires spending on business activities, especially at the introductory stage, such as promotion and product development costs. The results of data analysis shows that H6 is accepted, there is a positive and significant influence between social media marketing on the sustainability MSMEs.…”
Section: Figure 1 the Structural Equation Modelling Calculationsupporting
confidence: 84%
“…The results of data analysis shows that H5 is rejected, there is a negative and not significant influence on cost on the sustainability of MSMEs. This is in line with the research of (Orouji & Kafashan, 2017), which states that the sustainability of MSMEs requires spending on business activities, especially at the introductory stage, such as promotion and product development costs. The results of data analysis shows that H6 is accepted, there is a positive and significant influence between social media marketing on the sustainability MSMEs.…”
Section: Figure 1 the Structural Equation Modelling Calculationsupporting
confidence: 84%
“…A preliminary work by Cassetta et al (2020) mentioned that engaged adoption of e-business information and communication technology (ICT) in a business company showed that companies investing in various platforms of ICT have a greater placement towards e-business, while the company cites handicaps in linked with cost and delivery acquaintance with lower e-business involvement. Additionally, Orouji and Kafashan (2017) remarked that companies with many advantages over time report, including providing affordable costs and reaching new customers, tend to have higher e-business operations.…”
Section: Cost (Cos)mentioning
confidence: 99%
“…Using social media has benefited the efficiency of many businesses (Kraus et al ., 2019) as young SMEs have the ability to embrace it faster than corporations (Ojo et al ., 2019). This approach helps SMEs to achieve their business goals and profits (Sunday and Vera, 2018), giving them a cost advantage over other companies by promoting sustainability through the use of social media while maintaining costs, targeting new audiences and accomplishing businesses goals (Orouji and Kafashan, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%